ON {2,3}-HYPERIDENTITIES IN INVERTIBLE {2,3}-ALGEBRAS WITH A BINARY GROUP OPERATION - Ghumashyan, H. E. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In the present paper the invertible {2,3}-algebras with a binary group operation and with balanced first sort {2,3}-hyperidentities having length 4 are characterized.
Keywords: quasigroup; ternary quasigroup; hyperidentity; invertible algebra